2017
DOI: 10.1089/gg.2017.0014
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Stimulation Differentially Impacts Human Male and Female Antigen-Specific T Cell Anti-Tumor Function and Polyfunctionality

Abstract: Sex-specific differences exist in innate and adaptive immune responses and are mediated by hormone signaling. Estrogen is able to differentially modulate the development and differentiation of immune cells, including T cells. However, the effect of estrogen on T cell function, especially at concentrations other than physiological, remains controversial and incompletely understood. Immunotherapy is one of the most promising cancer treatments to date with a high probability of future enhancements. The adoptive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…This was due to male donor T-cell populations having a higher ratio of CD8:CD4 T cells compared to female donors. 100 This supported the conclusion that estrogen modulates differentiation of human single positive CD4/CD8 T cells, which is the reason that males and females show different ratios of T-cell subsets worldwide. 101 Furthermore, the same study also reported that estrogen treatment increased TNFa and IL-4 secretion on CD8 þ T cells of both males and females.…”
Section: Section 3: the Effect Of Estrogen On Antitumor Immunitysupporting
confidence: 66%
See 2 more Smart Citations
“…This was due to male donor T-cell populations having a higher ratio of CD8:CD4 T cells compared to female donors. 100 This supported the conclusion that estrogen modulates differentiation of human single positive CD4/CD8 T cells, which is the reason that males and females show different ratios of T-cell subsets worldwide. 101 Furthermore, the same study also reported that estrogen treatment increased TNFa and IL-4 secretion on CD8 þ T cells of both males and females.…”
Section: Section 3: the Effect Of Estrogen On Antitumor Immunitysupporting
confidence: 66%
“…101 Furthermore, the same study also reported that estrogen treatment increased TNFa and IL-4 secretion on CD8 þ T cells of both males and females. 100 The positive estrogen effect on IL-4 expression was shown to be completely dependent on ERa because once T cells were treated with estrogen in combination with MPP-dihydrochloride, which is a complete blockade of the ERa, IL-4 secretion was lowered to the level of unstimulated T cells in both males and females. 100 On the other hand, selectively blocking ERb had no effect on IL-4 expression, but it did have a positive effect on TNFa expression suggesting ERa/ERb competition for ligand binding, similar to the case of IFNg.…”
Section: Section 3: the Effect Of Estrogen On Antitumor Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to effects on DC, oestrogen may also influence T cell development 44 and the balance of CD4/CD8 activation. 45 Although CD4 + Tregs were responding to OVA across all groups, only in males were CD8 + T effector cells observed to respond. As CD8 + and CD4 + T cell populations can potentially cross-regulate each other, notably via the effects of Treg cells that are highly active in rats, the absence of CD8 activation in females and E2-treated males may result in excessive CD4 activation and subsequent Th2 inflammation in these groups, but this possibility was not tested.…”
Section: Discussionmentioning
confidence: 92%
“…It may also relate to the stable administration of E2 compared to the fluctuating levels in females as part of their oestrous cycle or the length of E2 administration. In addition to effects on DC, oestrogen may also influence T cell development and the balance of CD4/CD8 activation . Although CD4 + Tregs were responding to OVA across all groups, only in males were CD8 + T effector cells observed to respond.…”
Section: Discussionmentioning
confidence: 96%